Stunting prevention through posyandu in Margaasih - Awalia Latifa Mayda Ikrimah; Aulia Rahmawati; Farikha Diah Andini Hernowo Putri (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
There is still a stunting rate in Margaasih Village, so the village community is trying to reduce this rate with ongoing programs. The Posyandu program, one of the village health service programs running every month, seeks to reduce stunting rates. A team of Universitas Pendidikan Indonesia students conducted community service in Margaasih Village to help reduce stunting rates. One of the activities carried out by the service team is assisting ongoing village programs, namely the Posyandu program, counseling, and providing additional food. The team also implemented the program based on the results of surveys and problem identification carried out in Margaasih Village and assisted with PPosyandu activities in Margaasih Village, as well as providing additional food from processed catfish to help reduce stunting rates. The team also held counseling regarding complementary foods for breast milk with participant mothers who still have children aged infants to toddlers. It is hoped that this counseling can provide mothers with an understanding of what food preparations are suitable for babies and help reduce stunting rates.   Abstrak Masih terdapat angka stunting di Desa Margaasih, sehingga masyarakat desa berupaya untuk menurunkan angka tersebut dengan program yang sedang berjalan. Program Posyandu sebagai salah satu program layanan kesehatan desa yang berjalan setiap bulannya berupaya dalam menurunkan angka stunting. Tim mahasiswa Universitas Pendidikan Indonesia melakukan pengabdian di Desa Margaasih untuk membantu mengurangi angka stunting. Kegiatan yang dilakukan oleh tim pengabdian salah satunya adalah dengan membantu program desa yang sedang berjalan yaitu program Posyandu, penyuluhan, dan pemberian makanan tambahan. Tim juga melaksanakan program tersebut berdasarkan hasil survei dan identifikasi masalah yang telah dilakukan di Desa Margaasih dan membantu kegiatan posyandu di Desa Margaasih, serta memberikan makanan tambahan dari olahan ikan lele untuk membantu mengurangi angka stunting. Selain itu, tim juga mengadakan penyuluhan mengenai makanan pendamping asi dengan peserta ibu-ibu yang masih memiliki anak berusia bayi hingga balita. Penyuluhan ini diharapkan dapat memberikan pemahaman kepada ibu-ibu mengenai olahan makanan yang baik untuk bayi dan membantu menurunkan angka stunting. Kata Kunci: Pengabdian masyarakat; posyandu; stunting